Psychometric properties of a brief Spanish version of Stigmatizing Situations Inventory - Ortiz, Manuel S.; Gómez-Pérez, Daniela (Revista Mexicana de trastornos alimentarios, 2019)
Abstract Overweight and obese people are a frequent target of weight stigma. However, there are no Spanish-Language validated inventories measuring weight stigma situations. Therefore, we sought to validate a brief Spanish version of the Stigmatizing Situations Inventory (SSI) in a sample of Chilean adults. A psychometric study with 377 adults was designed (Mage = 45.0, SD = 8.7; 62% female). Twenty-four items available from two previous versions of the SSI developed were back-translated from English to Spanish, and semantically adapted to the Chilean sample. We explored the factorial structure with 173 participants, and then confirmed it with 204 subjects. We obtained evidence of concurrent validity with other psychological measures, as well as evidence of reliability. Our results identified a single factor structure grouping 10-items, with factorial loadings greater than .60. The overall fit indices are excellent. There is evidence of concurrent validity with body mass index (r = .43), anger (r = .19), anxiety (r = .29), and daily life discrimination (r = .26); all with p < .05. The reliability of our version is high (α = .91). The brief Spanish version of the SSI is a 10-items reliable and valid scale with one-dimensional factorial structure. This scale can be used by researchers and healthcare professionals studying psychological consequences of obesity.